A case of HIV at Woodworks Ltd (c) : epilogue - Sharda, Kirti (London : Indian Institute of Management, Ahmedabad, 2020)
All key positions in the Woodworks Ltd. factory were vacant. The factory that once used to run in two shifts, 24 hours, was now finding it impossible to run machines in even one shift. Production slowed down and some operations came to a standstill. Such were the repercussions of the dismissal of Plant Head, Raman Basu, from Woodworks Ltd. by Jai Shah, CEO. When Basu left, 11 of the efficient workers he had appointed also walked away from their jobs, probably, in a show of solidarity. Jai was concerned, but not dejected. He reasoned, "Whatever had to happen, happened".
Description based on XML content.
Keywords: elektronické knihy; electronic books; HIV-positive persons -- Employment; AIDS (Disease) -- Patients -- Employment; Personnel management; Social responsibility of business; Industrial productivity; Employee health promotion